The Emergency Surgery Score accurately predicts the need for postdischarge respiratory and renal support after emergent laparotomies: A prospective EAST multicenter study. Issue 3 (4th March 2021) - El Hechi, Majed; Kongkaewpaisan, Napaporn; Naar, Leon; Aicher, Brittany; Diaz, Jose; O'Meara, Lindsay; Decker, Cassandra; Rodriquez, Jennifer; Schroeppel, Thomas; Rattan, Rishi; Vasileiou, Georgia; Yeh, D. Dante; et al.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: The Emergency Surgery Score (ESS) was recently validated as an accurate mortality risk calculator for emergency general surgery. We sought to prospectively evaluate whether ESS can predict the need for respiratory and/or renal support (RRS) at discharge after emergent laparotomies (EL). METHODS: This is a post hoc analysis of a 19-center prospective observational study. Between April 2018 and June 2019, all adult patients undergoing EL were enrolled. Preoperative, intraoperative, and postoperative variables were systematically collected. In this analysis, patients were excluded if they died during the index hospitalization, were discharged to hospice, or transferred to other hospitals. A composite variable, the need for RRS, was defined as the need for one or more of the following at hospital discharge: tracheostomy, ventilator dependence, or dialysis. Emergency Surgery Score was calculated for all patients, and the correlation between ESS and RRS was examined using the c-statistics method. RESULTS: From a total of 1, 649 patients, 1, 347 were included. Median age was 60 years, 49.4% were men, and 70.9% were White. The most common diagnoses were hollow viscus organ perforation (28.1%) and small bowel obstruction (24.5%); 87 patients (6.5%) had a need for RRS (4.7% tracheostomy, 2.7% dialysis, and 1.3% ventilator dependence). Emergency Surgery Score predicted the need for RRS in a stepwise fashion; for example, 0.7%, 26.2%, and 85.7% of patients required RRS at an ESS of 2, 12, and 16, respectively. The c-statistics for the need for RRS, the need for tracheostomy, ventilator dependence, or dialysis at discharge were 0.84, 0.82, 0.79, and 0.88, respectively. CONCLUSION: Emergency Surgery Score accurately predicts the need for RRS at discharge in EL patients and could be used for preoperative patient counseling and for quality of care benchmarking. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III